Open innovation in Aida Furniture UKM in Pasuruan: A study on the influence of entrepreneurial founders on open innovation practices - Suparno; Sudarmiatin; Imam Mukhlis (Cita konsultindo, 2022)
The purpose of this research is to deepen our knowledge about the role of the